Anchee Min's Becoming Madame Mao and the Self-Constructed Heroine - Kui Ling, Emily Lau (Asiatic: IIUM Journal of English Language and Literature, 2016)
Anchee Min’s Becoming Madame Mao (2000), is a remarkable piece of historical fiction. Min’s choice of inter-textuality between history and fiction is apt as this quasi-poetic form allows for the possibility of delving into the psychological depths of the protagonist which fills the gaps in the existing historians’ biographies of Madame Mao. The marrying of history and fiction provides Min the subjectivity to penetrate deep into the protagonist’s thoughts and feelings, thus humanising even an outcast. This paper, through a feminist perspective, shows how Min renders a powerful tale of passion, betrayal and survival through the life story of Madame Mao. Min, through her writing, harnesses the power of language and the power of imagination as an instrumental and effective strategy to tap into the process of Madame Mao’s self-construction: from poverty and obscurity to professional success and fame.